The heart of Dōgen's Shōbōgenzō - Dōgen, 1200-1253 (State University of New York Press, 2002)
"The Heart of Dogen's Shobogenzo provides annotated translations of the difficult core essays of Shobogenzo, the masterwork of Japanese Zen master Dogen Kigen, the founder of Soto Zen. This book is centered around those essays that generations have regarded as containing the essence of Dogen's teaching. These translations, revised from those that first appeared in the 1970s, clarify and enrich the understanding of Dogen's religious thought and his basic ideas about Zen practice and doctrine. Dogen's uncommon intellectual gifts, combined with a profound religious attainment and an extraordinary ability to articulate it, make Shobogenzo unique even in the vast literature the Zen school has produced over the centuries, securing it a special place in the history of world religious literature."--Jacket